PREDICTING THE RELATIONSHIP BETWEEN PERCEIVED INFLUENCE, BRAND ENGAGEMENT, BRAND EXPECTED VALUE AND INTENTION PURCHASE: AN EMPRICAL STUDY - Destian F Amaldi; Bella Sugita; Sabrina O. Sihombing (Jurnal Manajemen Terapan dan Keuangan, 2021)
The purpose of this study is to predict the relationship between  perceived influence, brand engagement, brand expected value, and intention to purchase. The data were gathered from online respondents. The research questionnaire was built from previous research and  the research variables were measured by 5-point Likert scales. Before analyzing data for testing hypotheses, reliability and validity tests are performed first. Hypothesis testing is conducted by using structural equation modeling.The results show that there are four out of six hypotheses that are supported. This paper provides research discussion, limitation, and recommendation for future research